An energy method for rapid evaluation of high-cycle fatigue parameters based on intrinsic dissipation. (November 2015) - Guo, Qiang; Guo, Xinglin; Fan, Junling; Syed, Rizwanulhaque; Wu, Chengwei
Highlights: We establish a calculation model of intrinsic dissipation. We propose an energy method for rapid evaluation of high-cycle fatigue parameters. Intrinsic dissipation can be an accurate indicator to describe fatigue damage. Two generation mechanisms of intrinsic dissipation is identified by analyses. Abstract: The present paper, firstly, establishes a calculation model of intrinsic dissipation, based on the double exponential regression for the one-dimensional distribution of specimen surface temperature variation. Then, an energy method is proposed for rapid evaluation of high-cycle fatigue parameters (i.e., fatigue limit and S – N curve). The energy method takes intrinsic dissipation as the fatigue damage indicator, and eliminates the interference of internal friction causing no damage on fatigue life evaluation. An experimental research on FV520B stainless steel was performed, in order to verify the feasibility and validity of the energy method, as well as the calculation model.